Star network model / Mastura Abd Malek - Abd Malek, Mastura (1997)
Nowadays information are significant for every activities. Doctors need to up-date reports on medical discovery, lawyers want historie facts on previous cases, teachers need latest information on current subject teaches in school and so on. Computers are the essential devices for those people to communicate through the world or to each other. Network allow many users to share a common pathway and communicate with each other. The main objective of thïs paper is to described the implementation of star network environment via RS-232. 3 personal computers with installed C compiler are connected using RS-232 cable to form a star network. One of which will act as a server and the other 2 will act as clients. The cliënt server software development is also described.